2-HYDROXY-4-METHOXYBENZALDEHYDE, AN ASTOUNDING FOOD FLAVORING METABOLITE: A REVIEW - Rathi, Neelima; Harwalkar, Keerthana; V, Jayashree; Sharma, Ashwani; Rao, Nagashree N (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Rich endowment of traditional knowledge plays a critical role in health care, food security, culture, environment and development. Traditional knowledge is also widely used by the aromatic, flavoring, food and health industries. Plant-based traditional medicine has often been used to identify and fast-track the development of modern food and drugs. Plants synthesize such wide array of secondary metabolites that includes alkaloids, glucosinolates, terpenoids and phenylpropanoids. This study is aimed to review on indigenous and exotic medicinal plants containing an astounding food flavoring metabolite; 2-hydroxy-4-methoxybenzaldehyde (HMB). Material and Method: The review focuses on the isomer of vanillin, 2-hydroxy-4-methoxybenzaldehyde, also called MBALD, HMB, or 2H4MB, a flavor compound that is generally found in the roots and rhizomes of medicinal plants. This food flavoring phenylpropenoid is one of the least investigated isomers of vanillin. HMB is known to exhibit a wide array of medicinal properties. Though the molecular role of these metabolites remains largely unknown, they are known to play a key role in plant-environment interactions/stress response/defence signaling and application in pharmaceutical and nutraceutical industries. Discussion and Conclusion: One of the key secondary metabolites is the group of phenylproponoids synthesized either through shikimic acid pathway or the malonate/acetate pathway. Phenylalanine ammonia lyase (PAL) is the enzyme involved in phenylpropanoid pathway catalysing the deamination of phenylalanine to synthesize cinnamic acid that subsequently synthesizes variety of phenylpropanoid products. Inspite of its medicinal importance, the regulatory molecular mechanism underlying the biosynthetic pathway is largely unknown.